PEMANFAATAN LIMBAH PERIKANAN SEBAGAI PRODUK NILAI TAMBAH DI PONDOK PESANTREN NURUL HUDA SURABAYA - Lailatul Lutfiyah; M Amin Alamsjah; Rr Juni Triastuti; Dwitha Nirmala (Jurnal Abdi Insani, 2023)
The use of fishery waste emphasizes a cyclical system in the production process, thereby creating clean production. Shrimp waste can pollute the environment around the factory so it needs to be utilized. One of the processing methods that can be done using shrimp heads is to make flavour. Islamic boarding schools and economic independence in an effort to develop Islamic boarding schools - are two things that cannot be separated. Training on fishery waste processing is one method to support economic independence in the form of entrepreneurship in Islamic boarding schools. Processing fishery product waste is an activity carried out in stages, sequentially, cleanly and hygienically, and meets quality requirements in order to convert fishery product waste into value-added products. The target of this community service activity is to establish a solid fishery waste processing business activity at the Nurul Huda Islamic Boarding School in Surabaya and be able to compete in the market continuously. The method used is an approach method that includes, among others, the Participatory method. The results that have been obtained from this activity are an increase in the knowledge of Islamic boarding school students about fishery waste, namely shrimp heads which are used as a flavouring/flavoring ingredient for safe cooking. The activity was attended by 43 students, with educational levels namely middle school and high school. Based on questionnaire data distributed, before the training was carried out, it was found that 93% of the students did not know that shrimp head waste could be used as a flavour. After the training, it was found that 94% of students were interested in making their own flavor production made from shrimp heads.